2020
DOI: 10.1111/eve.13395
|View full text |Cite
|
Sign up to set email alerts
|

Gait abnormalities and ridden horse behaviour in a convenience sample of the United Kingdom ridden sports horse and leisure horse population

Abstract: Summary The objectives of this study were to compare horses’ gaits in hand and when ridden; to assess static and dynamic saddle fit for each horse and rider; to apply the Ridden Horse Pain Ethogram (RHpE) and relate the findings to gait abnormalities consistent with musculoskeletal pain, rider position and balance and saddle fit; and to document noseband use and its relationship with mouth opening during ridden exercise. Data were acquired prospectively from a convenience sample of horses believed by their own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(50 citation statements)
references
References 35 publications
0
47
2
1
Order By: Relevance
“…As hypothesised the median RHpE score was low, consistent with the absence of many of the signs associated with musculoskeletal pain in the majority of horses, and a relatively narrow spectrum of behaviours was observed compared with lame horses [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The most frequently observed behaviours were the front of the head being behind a vertical position >10° for ≥10 s, mouth opening with separation of the teeth for ≥10 s, an intense stare for ≥5 s and repeated tail swishing, similar to the most common behaviours observed in elite event horses during the warm-up for the dressage phase at 5* three-day events [ 9 ].…”
Section: Discussionmentioning
confidence: 52%
See 4 more Smart Citations
“…As hypothesised the median RHpE score was low, consistent with the absence of many of the signs associated with musculoskeletal pain in the majority of horses, and a relatively narrow spectrum of behaviours was observed compared with lame horses [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. The most frequently observed behaviours were the front of the head being behind a vertical position >10° for ≥10 s, mouth opening with separation of the teeth for ≥10 s, an intense stare for ≥5 s and repeated tail swishing, similar to the most common behaviours observed in elite event horses during the warm-up for the dressage phase at 5* three-day events [ 9 ].…”
Section: Discussionmentioning
confidence: 52%
“…A Ridden Horse Pain Ethogram (RHpE) comprising 24 behaviours, the majority of which are at least 10 times more likely to be seen in lame versus non-lame horses, has previously been developed [ 1 ]. It has been shown that a RHpE score ≥8 is likely to reflect the presence of musculoskeletal pain [ 1 , 2 , 3 , 4 , 5 , 6 ]. Removal of pain by diagnostic anaesthesia results in significant reductions in RHpE scores [ 2 , 3 ], indicating a causal relationship between behaviour and pain.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations